Assessing Market Efficiency and Behavioral Anomalies in Financial Markets - Muhammad Hidayat (STIE Amkop Makassar, 2024)
This study explores the interaction between market efficiency and behavioral anomalies in financial markets, aiming to provide insights into investment strategies and market dynamics. The purpose of the research is to examine deviations from the Efficient Market Hypothesis (EMH) by investigating anomalies like the momentum effect and the value effect. Employing surveys and interviews, the study scrutinizes the impact of behavioral biases such as overconfidence and herding behavior on investor decision-making. Findings reveal persistent anomalies challenging EMH assumptions, with behavioral biases significantly influencing market outcomes. Implications suggest the need for adaptive investment strategies that integrate behavioral insights, emphasizing the importance of investor education and regulatory measures to mitigate the adverse effects of irrational behavior. This research underscores the evolving nature of financial markets and advocates for a holistic approach that incorporates both market efficiency theories and behavioral finance principles to enhance market transparency and investor welfare.